2020
DOI: 10.3389/fpsyg.2020.00062
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Leadership and Taking-Charge Behavior: Roles of Psychological Safety and Thriving at Work

Abstract: Taking charge is an important form of proactive behavior that sustains organizational survival and individual development. Learning how to motivate employees to engage in taking-charge behavior has become one of the hot topics in the field of organizational management. Despite considerable research investigating the factors influencing taking charge, less attention has been paid to leadership-related factors, such as inclusive leadership. Based on the self-determination theory and the social information proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
113
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(130 citation statements)
references
References 76 publications
(104 reference statements)
14
113
1
2
Order By: Relevance
“…This research further expands our knowledge of the contextual antecedents of adaptive performance in organizations and could inspire leaders to establish mentoring to promote thriving at work among employees, thereby continuously improving individual adaptive performance. Furthermore, organizations should take measures to motivate employees' promotion focus, such as providing job opportunities and inclusive leadership (Zeng et al, 2020). In summary, this study provides useful insights for both theory and practice.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This research further expands our knowledge of the contextual antecedents of adaptive performance in organizations and could inspire leaders to establish mentoring to promote thriving at work among employees, thereby continuously improving individual adaptive performance. Furthermore, organizations should take measures to motivate employees' promotion focus, such as providing job opportunities and inclusive leadership (Zeng et al, 2020). In summary, this study provides useful insights for both theory and practice.…”
Section: Resultsmentioning
confidence: 90%
“…The research has shown that positive emotions have a positive impact on employees' changes and proactive behavior in the presence of certain risks (Bindl et al, 2012). Relevant research has also verified the positive correlation between thriving at work and employee-oriented citizenship behavior (Li et al, 2016) and taking charge behavior (Zeng et al, 2020). Therefore, the vitality experienced by the protégé and the related positive affects can further enhance willingness to adapt (Pulakos et al, 2002;Chen et al, 2005).…”
Section: Mediating Role Of Thriving At Workmentioning
confidence: 88%
“…Resilient leaders are accomplished in guiding members to gain a positive emotion, leading the team to go through the adverse situation and setbacks ( Masten and Reed, 2002 ). To sum up, high PsyCap leaders play a key role in establishing a relationship of faithfulness, harmony, and mutual trust among team members, and the organizational atmosphere of equality, tolerance, and trust helps to improve the employees’ sense of psychological safety ( Zeng et al, 2020 ). Accordingly, this study hypothesized that leader PsyCap positively affects psychological safety among employees and proposed the following hypotheses:…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Therefore, our study not only theoretically explored the interaction effect of affective commitment and traditionality on follower taking charge but also empirically explored the moderating role of traditionality in the relationship between affective commitment and follower taking charge, which response to calls for "the combined influence of individual factors and the organizational context". 6,23 Practical Implications…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…17 Previous studies have shown that leadership behavior is an important predictor of taking charge. 5,[18][19][20][21][22] Although Zeng et al 23 examined the relationship between inclusive leadership and taking charge, which was based on the perspective of self-determination and social information processing to explain the influence of inclusive leadership on taking charge, but ignored the emotional factors of employees. Because it is not a simple contractual exchange relationship between employees and organizations, and their interaction process is often mixed with complex emotional factors, 24,25 which is difficult to systematically explain the effect of inclusive leadership on taking charge from a cognitive perspective.…”
Section: Introductionmentioning
confidence: 99%